(untitled) (Bioscience Journal, 2009)
The effects of swine manure fertilization on the water quality of zooplankton-culture artificial in two ponds were measured a diel cycles in different months (October 1999, January and March 2000). Fertilization affected directly water quality; values for total phosphorus were above 2 mgL-1 and maximum values for ammonia reached 132 ï?gL-1. Zooplankton community was just represented by four species Brachionus calyciflorus, B. falcatus, Moina sp, and Thermocyclops sp. B. falcatus (Rotifera), which were dominant in January whereas Moina sp (Cladocera) was dominant in March. The omnivorous cyclopoid Thermocyclops sp was also favored in fertilized plankton ponds despite not being an ideal organism to be used as food for fish post-larvae. There were significant differences between treated and control plankton ponds (p